Clozapine Treatment and Offending: A Within-Subject Study of Patients With Psychotic Disorders in Sweden - Bhavsar, Vishal; Kosidou, Kyriaki; Widman, Linnea; Orsini, Nicola; Hodsoll, John; Dalman, Christina; MacCabe, James H (Schizophrenia bulletin, 2020)
Abstract Clozapine treatment may have beneficial effects on behavioral outcomes in psychotic disorders, including violent offending. Although clozapine and other antipsychotics have been linked to lower levels of violent behavior, these have been primarily in small selected samples, and population-based estimates have been limited and imprecise. We aimed to assess the effect of clozapine treatment on the rate of violent and nonviolent offending. We carried out a within-person mirror-image study of the Swedish population with linked prescription, hospitalization, and sociodemographic registers. Outcomes were violent, nonviolent, and overall offences occurring before and after clozapine, or olanzapine, initiation. Comparison of effects of clozapine and olanzapine on key variables was modeled with interaction terms. We found periods of mirror-image observation time with clozapine treatment were associated with a much lower rate of violent offending compared to periods before treatment (rate ratio [RR]: 0.13 (95% CI: 0.05, 0.34). Reductions in nonviolent offences were smaller in magnitude (RR: 0.37, 95% CI: 0.17, 0.80). There was a statistically greater rate reduction effect on violent offences for clozapine than olanzapine (RR for interaction: 4.84, 95% CI: 1.56, 14.86, P = .002). In patients with psychotic disorders, clozapine treatment is associated with a lower rate of violent offending compared to olanzapine.